Given that: y = 3x^2 + 6x^1/3 + (2x^3 - 7)/(3x^1/2), x > 0 Find dy/dx, give each term in its simplest form

y = 3x2 + 6x1/3 + (2x3/3 - 7/3)x-1/2Using the multiplication rule for indices y = 3x2 + 6x1/3 + (2/3)x5/2 - (7/3)x-1/2Then differentiate each term with respect to x to find dy/dxdy/dx = 6x + 2x-2/3 + (10/6)x3/2 + (7/6)x-3/2Then simplify each term, as requested in the questiondy/dx = 6x + 2/x2/3 + (5/3)x3/2 + 7/6x3/2

Related Maths A Level answers

All answers ▸

∫2x(x+2)^(1/2) dx evaluated from 0->2


f(x) = x^3 + 3x^2 + 5. Find f'(x) and f''(x).


find dy/dx for the equation y = 6x ^(1/2)+x+3


Rewrite (2+(12)^(1/2))/(2+3^(1/2)) in the form a+b((c)^(1/2))


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences